2015
DOI: 10.1016/j.jcorpfin.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Corporate efficiency in Europe

Abstract: Using a stochastic frontier model and a comprehensive dataset, we study factors that affect corporate efficiency in Europe. We find that (i) larger firms are less efficient than smaller firms, (ii) greater leverage contributes to corporate efficiency, and (iii) high competition is less conductive to efficiency than moderate or low competition. In terms of ownership, we find that (iv) efficiency increases when a majority owner must deal with minority shareholders and that (v) domestic majority owners improve ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 87 publications
(96 reference statements)
4
44
0
1
Order By: Relevance
“…standard and circumvents the issue of dispersed ownership that was shown to play no role with respect to firms' efficiency specifically in the European context (Hanousek et al, 2015) The construction of all key variables that characterize potential effects of the FDI in the upstream and downstream sectors used in our regressions is explained in the Appendix Tables A1 and A2, respectively. Both tables also contain precise information on the sources and units used.…”
Section: Definition Of Variables and Resulting Datasetmentioning
confidence: 99%
“…standard and circumvents the issue of dispersed ownership that was shown to play no role with respect to firms' efficiency specifically in the European context (Hanousek et al, 2015) The construction of all key variables that characterize potential effects of the FDI in the upstream and downstream sectors used in our regressions is explained in the Appendix Tables A1 and A2, respectively. Both tables also contain precise information on the sources and units used.…”
Section: Definition Of Variables and Resulting Datasetmentioning
confidence: 99%
“…It is able to identify critical aspects endangering fi rm´s future and, on the other hand, it also may reveal strengths which can, when maintained and boosted, help a company become more sustainable and competitive (Hiadlovský et al, 2016). Hereby, to take right decisions, managers need to analyse their fi nancial situation, especially in respect to fi rm´s profi tability and the factors infl uencing it (Emery et al, 2007;Atrill, 2006;Hanousek et al, 2015;Zalai et al, 2016;Park & Youngtae, 2017;Beyer & Hinke, 2018). As profi t maximisation is generally one of the most signifi cant fi nancial objectives, managers try to take decisions supporting its achievement.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Measurement of profi tability is most frequently based on the construction of profi tability indicators, which take the form of ratios. One can say that the profi tability ratios show effi ciency of the overall business activity (Higgins, 2003;Gibson, 2012;Cumming & Groh, 2018). With the help of them, the intensity of the use, reproduction and recovery of capital invested in the fi rm are expressed (Maynard, 2013).…”
Section: ľUbica Lesáková Andrea Ondrušová Miroslava Vinczeovámentioning
confidence: 99%
See 1 more Smart Citation
“…Hanousek et al (2015) examined corporate efficiency in old and new Europe and concluded that majority ownership does not ensure efficiency.4 The question of how differences in the types of owners and privatization methods employed can affect firm performance in transition economies has been examined byIwasaki and Mizobata (2018) by using a meta-analysis approach similar to the one described herein. 5 A meta-analysis conducted byHeugens et al (2009), on the other hand, included only studies focusing on companies in Asia.6 These emerging markets include 14 counties in South America, Asia, the Middle East, and Africa and the four CEE/FSU countries (i.e., the Czech Republic, Hungary, Poland, and Russia).…”
mentioning
confidence: 99%